QUASI-STATIC ANALYSIS OF MICROSTRIP LINES WITH INFINITELY THIN METALLIZATION THICKNESS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents a modified hybrid boundary element method (HBEM) approach for analysing microstrip lines with negligible metallization thickness. The proposed method enhances computational efficiency while maintaining high accuracy in determining transmission parameters such as characteristic impedance and effective permittivity. Numerical results validate the method’s capability for analyzing both single and coupled microstrip lines with infinitely thin strip conductors, showing a maximum deviation of less than 1.3% from established approaches like the equivalent electrodes method (EEM) and finite element method (FEM). The developed approach enables the efficient modeling of microstrip structures where the conductor thickness is negligible, making it particularly useful in theoretical studies and the design optimization of microwave circuits, where metallization thickness has a minimal impact.
Keywords: Characteristic impedance; Effective relative permittivity; Finite element method; Hybrid boundary element method; Microstrip lines